Convergence strategy and innovation capability of the classic art industry - SeongBae Lim; Hong-Hee Lee; Kyoung Claudio Jung (International Journal of Quality Innovation, 2020)
Arts management is the field related to business operations of arts organizations, specifically production, fundraising, policy and administration, public relations, marketing, etc. The main characteristic of the field of art is that it requires talented people as the main input for value creation, and this requires effective management of resources and processes. The purpose of this study is to investigate the potential of a convergence strategy for improving the sustainability of the opera industry by focusing on operama, a new genre created through the fusion of opera and drama. Through the convergence of the two different industries, operama has been able to communicate the philosophy and artistic values of classic art to the public more effectively. This study proposes how classic art industries can be positively reinvented by adopting various convergence strategies.
Keywords: 650; Art management; Classic art industry; Convergence strategy; Operama